2022
DOI: 10.3390/computation10020014
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Survey of the UV–Visible Spectra of Axially and Peripherally Substituted Boron Subphthalocyanines

Abstract: The UV–visible spectra of a series of subphthalocyanines (SubPcs) characterized by three different axial substituents (An) in combination with H, F, NO2, SO2H and SO2CH3 peripheral substituents (Ri) were predicted and analyzed by means of time-dependent DFT calculations, including chloroform as a solvent. In this analysis, we paid particular attention to the Q band, which remained almost unchanged regardless of the nature of the axial substituent. For the same axial substituent, changes in the Q band were also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Geometry, electronic structure, electrochemical and spectroscopic features of SubPcs have been thoroughly investigated by theoretical calculations. 211–233 A detailed study on a series of three SubPc-Cl derivatives bearing different peripheral substituents ( i.e. perhydrogenated, trinitro- and tri- t -butyl SubPc) at Hartree–Fock (HF) and density functional theory (DFT) levels using STO-3G and 6-31G basis sets has been reported by Ferro et al 211 The calculated geometries of the unsubstituted derivative were found to be in accordance with the experimental data from X-ray diffraction studies, and no substantial changes were detected with respect to the substituted derivatives.…”
Section: Subphthalocyaninesmentioning
confidence: 60%
“…Geometry, electronic structure, electrochemical and spectroscopic features of SubPcs have been thoroughly investigated by theoretical calculations. 211–233 A detailed study on a series of three SubPc-Cl derivatives bearing different peripheral substituents ( i.e. perhydrogenated, trinitro- and tri- t -butyl SubPc) at Hartree–Fock (HF) and density functional theory (DFT) levels using STO-3G and 6-31G basis sets has been reported by Ferro et al 211 The calculated geometries of the unsubstituted derivative were found to be in accordance with the experimental data from X-ray diffraction studies, and no substantial changes were detected with respect to the substituted derivatives.…”
Section: Subphthalocyaninesmentioning
confidence: 60%
“…We can notice the large panel of scientific topics covered by Karlheinz's knowledge. We deeply acknowledge the following contributions related to spectroscopy by Manuel Yañez et al [12], Juan-Carlos Sancho-García and Emilio San-Fabián [13]; excited states by Ágnes Nagy [14], Kalidas Sen et al [15] and Fabrizia Negri et al [16]; DFT developments by Fabio Della Sala et al [17], Mathias Rapacioli and Nathalie Tarrat [18], Emmanuel Fromager et al [19], José Manuel García de la Vega et al [20] and Harry Ramanantoanina [21]; results analysis by Andreas Savin et al [22] and Manuel Richter et al [23]; and, of course, the solid state and surfaces by Leila Kalantari and Fabien Tran et al [24], Denis Salahub et al [25], Peter Blaha et al [26], Samuel B. Trickey [27], William Lafargue-Dit-Hauret and Xavier Rocquefelte [28], Tzonka Mineva and Hazar Guesmi et al [29]. (H.C.)…”
mentioning
confidence: 99%